2022
DOI: 10.1021/acscatal.2c00552
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of βPdZn Alloy in Pd/ZnO Catalysts for the Hydrogenation of Carbon Dioxide to Methanol

Abstract: The rise in atmospheric CO 2 concentration and the concomitant rise in global surface temperature have prompted massive research effort in designing catalytic routes to utilize CO 2 as a feedstock. Prime among these is the hydrogenation of CO 2 to make methanol, which is a key commodity chemical intermediate, a hydrogen storage molecule, and a possible future fuel for transport sectors that cannot be electrified. Pd/ZnO has been identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…A linear relationship between CO2 conversion and methanol selectivity has recently been demonstrated for Pd/ZnO catalysts prepared through a variety of techniques, 24 this linear relationship is shown by the PdZn line on Figure 2. In addition to the alloy, a recent study has shown the presence of a ZnO phase to be important for achieving high methanol productivity, 25 which may explain the high activity of the Pd/ZnO catalysts.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…A linear relationship between CO2 conversion and methanol selectivity has recently been demonstrated for Pd/ZnO catalysts prepared through a variety of techniques, 24 this linear relationship is shown by the PdZn line on Figure 2. In addition to the alloy, a recent study has shown the presence of a ZnO phase to be important for achieving high methanol productivity, 25 which may explain the high activity of the Pd/ZnO catalysts.…”
Section: Resultsmentioning
confidence: 79%
“…Furthermore, the importance of controlling PdZn particle size was highlighted, with methanol selectivity decreasing from 60 % to 20 % upon increasing the PdZn particle size from 3 to 7 nm. More recently, Pd/ZnO catalysts prepared by a range of techniques were investigated for CO2 hydrogenation; 24 here it was shown that the β-PdZn alloy was formed for all materials, regardless of preparation method. This was attributed to the favourable heat of mixing for the β-PdZn 1:1 alloy, as determined by DFT studies.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…As shown in Figure 5 , there is a broad peak at 2θ = 20°−25°, in all XRD patterns that is attributed to the characteristic diffraction peak of amorphous carbon [ 45 ]. For the patterns of samples were carbonized at 650 and 800°C, i.e., Pd–Zn-ins/CNS-650, Pd–Zn-ins/CNS-800, the diffraction peaks, located at 2θ = 26.8°, 30.8°, 41.2°, 44.1°, 55.2°, 64.2°, 72.9 and 79.2° correspond to the lattice planes of (001), (110), (111), (200), (002), (112), (310) and (311) of PdZn, respectively [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. No diffraction peaks of individual palladium and zinc or their oxides were detected.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was found that supported palladium–zinc alloy catalysts exhibited high performance for the hydrogenation of acetylene in the front-end hydrogenation process [ 33 , 34 , 35 , 36 , 37 ]. According to the literature, the type of Pd–Zn intermetallics (Pd–Zn-ins) in catalysts dramatically affected the activity and selectivity of specific catalytic reactions [ 38 , 39 , 40 , 41 ]. However, to the best of our knowledge, the synthesis of a serial of Pd–Zn-ins and the discussion of the effect of the intermetallic type on selective hydrogenation of acetylene have not been reported.…”
Section: Introductionmentioning
confidence: 99%